2013
DOI: 10.1186/1472-6823-13-26
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of interleukin-21 and interleukin-21-receptor genes confer risk for autoimmune thyroid diseases

Abstract: BackgroundThe abnormality of interleukin-21 (IL-21)-IL-21-receptor (IL-21R) system has been found in many autoimmune diseases including autoimmune thyroid diseases (AITDs). In this study, we investigated whether polymorphisms of the IL-21 and IL-21R are associated with Graves’ disease (GD) and Hashimoto’s thyroiditis (HT), two major forms of AITDs, among a Chinese population.MethodsRs907715, rs4833837, rs2221903 and rs2055979 of the IL-21 gene and rs3093301 and rs2285452 of the IL-21R gene were explored in a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 18 publications
2
30
1
Order By: Relevance
“…In addition, You et al have reported that The IL-21 −2498A allele predicts longer 5-year survival in breast cancer patients [19]. Our data showed that −2498GA and AA genotypes were associated with decreased susceptibility to DLBCL in the Chinese population ( [20]. However, we did not identify any correlation between IL-21 +78A/G SNP and DLBCL in our study population.…”
Section: Discussioncontrasting
confidence: 74%
“…In addition, You et al have reported that The IL-21 −2498A allele predicts longer 5-year survival in breast cancer patients [19]. Our data showed that −2498GA and AA genotypes were associated with decreased susceptibility to DLBCL in the Chinese population ( [20]. However, we did not identify any correlation between IL-21 +78A/G SNP and DLBCL in our study population.…”
Section: Discussioncontrasting
confidence: 74%
“…The patients with the AA genotype of IL-21R rs2285452 show higher risk of HBV-related HCC than those with the AG/GG genotype. In a previous study, the IL-21R rs2285452 polymorphism showed differential genotype distribution in Hashimoto's thyroiditis (HT) and control subjects [40]. Moreover, the IL-21 rs2221903 and IL-21R rs3093301 polymorphisms were associated with chronic HBV infection, an interactive role of IL21R rs3093301 CC with IL21 rs2221903 in inducing the elevation of IL-21 and IgE production in the HBV patients, thereby suggesting that the SNPs in the IL-21 and IL-21R genes influence the susceptibility and persistence of HBV by affecting serum IL-21 and IgE levels [38].…”
Section: Discussionmentioning
confidence: 97%
“…About 25-50 % of GD patients have clinical signs of Graves' ophthalmopathy (GO), most having mild disease [2,3]. Genome-wide screens conducted in GD have identified a number of putative susceptibility genes in GD [4] and several gene loci have been reported to be associated with a risk of developing GD, including HLA [4,5], CTLA4 [6], PTPN22 [7], CD40 [8], IL2RA [9], IL21 [10], and TG [11]. About 20 identified genetic polymorphisms, including both thyroid-specific genes and those regulating the autoimmune response were already investigated.…”
Section: Introductionmentioning
confidence: 98%